Kiasan-Kiasan pada Teks Berita Tribun Jateng sebagai Alternatif Bahan Ajar di SMA - Ajeng Nur Muslikhah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to describe allusions in the news text of the Central Java Tribune as an alternative teaching material in high school. This type of research is descriptive qualitative. Data collection was carried out using the note-taking research method, selecting news texts that used figurative language styles and listening carefully, directed and carefully to primary data sources. Based on the news text, the news text 'Up Again! Complete Fuel Prices Throughout Indonesia Thursday 13 April 2023 Check Central Java Prices' taken from the April 2023 edition of the Central Java Tribune website found the use of metaphor, metonomia and allegory. In relation to its suitability as an alternative teaching material in high school based on suitability to students' cognition, suitability to character education, suitability to students' language, psychological aspects, and cultural background aspects, the use of figurative language styles in news texts is suitable for use as an alternative teaching material. in high school and references that help Indonesian language subject teachers in appreciating Indonesian literary works, especially in prose.